MANAJEMEN SUBDURAL HEMATOMA KRONIS: SEBUAH PARADIGMA BARU STRATEGI NEUROINTERVENSI - Fritz S. Usman; Graha Agung Mulyono; Beny Rilianto; Hendra Irawan; Nasrul Irawan; Gunawan Septa Dinata; Erwin Joe (PERDOSNI, 2021)
Chronic Subdural Hematoma (cSDH) is a significant challenge in neurology; it causes high morbidity and mortality rates and a high risk of recurrence. The primary mechanism of cSDH is the microhemorrhage caused by the repeated cycle of inflammation and angiogenesis. Treatment options for cSDH vary from conservative management, surgical therapy, endovascular strategy, or any combination. The endovascular strategy for cSDH management is embolizing the middle meningeal artery. This strategy gives neurologists a promising treatment option, as it proposes a minimally invasive option or, in conjunction with surgery, can prevent recurrences. In addition, middle meningeal artery embolization can also be done in a frail, elderly patient who will not tolerate an extensive craniotomy procedure; the procedure provide earlier ambulatory, which minimalizes hospital cost. Keywords: Chronic Subdural Hematoma, endovascular strategy, middle meningeal artery embolization